The first chiral HPLC separation of dicarba-nido-undecarborate anions and their chromatographic behavior - Horáček, Ondřej; Papajová-Janetková, Monika; Grüner, Bohumír; Lochman, Lukáš; Štěrbová-Kovaříková, Petra; Vespalec, Radim; Kučera, Radim (Talanta, 2021)
Boron cluster compounds are extensively studied due to their possible use in medicinal chemistry, mainly in the boron neutron capture anticancer therapy and as new innovative pharmacophores. Concerning this research, the chiral separations of exceptionally stable anionic 7,8-dicarba-nido-undecaborate(1-) and metal bis(dicarbollide(1-) derivatives with asymmetric substitutions remain the unsolved challenge of the chiral chromatography nowadays. Although the successful enantioseparation of some anionic 7,8-dicarba-nido-undecaborate(1-) ion derivatives were achieved in CZE with native β-cyclodextrins, it has not been observed with HPLC, yet. This study aimed to systematically investigate the enantioseparation of selected compounds in HPLC using native β-cyclodextrin and brominated β-cyclodextrin. The findings revealed positively charged strong adsorption sites on a stationary phase, identified as the cationic metal impurities in the silica-gel backbone. All the anionic species under the study were at least partially enantioseparated when a chelating agent blocked these cationic sites. Consequently, the first-ever HPLC enantioseparations of the 7,8-dicarba-nido-undecaborates(1-) were achieved. The brominated β-cyclodextrin seemed to be a better chiral selector for separation of these species, whereas the native β-cyclodextrin separated the anionic cobalt bis(dicarbollide(1-). The results of this study bring new information concerning the chiral separation of anionic boron clusters and might be used in the chiral method development process on other chiral selectors. Furthermore, the possibility of chiral separation of these species could influence the ongoing research areas of anionic boron clusters.
Keywords: Boron Compounds; sloučeniny boru; Chromatography, High Pressure Liquid; kationty; stereoizomerie; Cations; Cyclodextrins; Carboranes; Ion interactions; Chiral separation; Cyclodextrin; Chromatography; vysokoúčinná kapalinová chromatografie; cyklodextriny; anionty; Stereoisomerism; Anions